2012
DOI: 10.1111/j.1468-5906.2011.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

“God Must Have Been Sleeping”: Faith as an Obstacle and a Resource for Rwandan Genocide Survivors in the United States

Abstract: In 1994, 1 million Rwandans were violently killed in only 100 days. Devastating for some Rwandan survivors was the significant role that some Catholic parishes and leaders took in ignoring, facilitating, and even perpetuating the genocide. This article seeks to understand how Rwandan genocide survivors draw on religion as they negotiate their postgenocide identities in the United States and comprehend their current faiths, beliefs, and practices. Based on qualitative interviews with Rwandan survivors now locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Several included studies describe churches, mosques and temples as places where individuals may receive opportunities to reconnect to practices and resources that are specific for the community, for example rituals and celebration of holidays. In some instances, the religious group may gather and meet on a regular basis, and provide a platform for interaction and practical help for members of the (sometimes ethnically organized) congregations [51,62,82,85]. As a consequence, participation in religious activities can be a source of emotional support, meaning-making and acceptance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several included studies describe churches, mosques and temples as places where individuals may receive opportunities to reconnect to practices and resources that are specific for the community, for example rituals and celebration of holidays. In some instances, the religious group may gather and meet on a regular basis, and provide a platform for interaction and practical help for members of the (sometimes ethnically organized) congregations [51,62,82,85]. As a consequence, participation in religious activities can be a source of emotional support, meaning-making and acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect contributing to psychosocial well-being or lack of such was the sense of belonging in the host country in a broader sense. Sense of belonging was, moreover, associated with engagement in civic rights activism [90], educational programs [91] and participation in other formal and informal social domains [34,38,48,58,82]. On the other hand, refugee status in contrast to other immigrants [32] and long process of asylum applications were found to have a negative effect on psychosocial well-being [37] through deprivation of sense of attachment and belonging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed persons who used aggressive, distancing, or exiting strategies toward their religion or toward the sacred were more likely to experience lasting negative effects of spiritual struggle (Exline, Kaplan, and Grubbs ). Additionally, at times, religiosity may be simultaneously an obstacle and a resource, as interviews with Rwandan genocide survivors showed (Fox ).…”
Section: Literature Reviewmentioning
confidence: 99%